Comparative study between WIDAL and DOT ELISA in the diagnosis of Typhoid fever - Hassan, Sarah; Khare, Vineeta; Yaqool, Shadma; Asghar, Syed Abid; Singh, Mastan; Siddiqi, Zeba (Asian Journal of Medical Sciences, 2021)
Background: Typhoid fever, also known as enteric fever, is a communicable disease, found only in man and occurs due to systemic infection mainly by Salmonella typhi organisms. Blood culture is regarded as the gold standard for diagnosis and carry 70-75% diagnostic yield in the first week of illness. Aims and Objective: To compare the sensitivity and specificity of Widal test and dot ELISA with blood culture in the early diagnosis of Typhoid fever. Materials and Methods: A Cross-Sectional study was carried out in the Department of Microbiology, Era’s Lucknow Medical College and Hospital for a period of 18 months. Patients presenting with acute febrile illness suspicious of typhoid fever accompanied by clinical signs and symptoms of typhoid fever in the absence of any other known febrile illnesses, were included in the study. Widal and Dot ELISA was performed using serum samples and for blood culture aseptically collected blood was used. Results: Sensitivity, Specificity, PPV, NPV of DOT ELISA as compared to Blood culture for typhoid positivity was found to be 92.6%, 83.7%, 55.6% and 98.1% respectively. Diagnostic accuracy of DOT ELISA as compared to Blood culture was found to be 85.3%. Conclusion: For both early and late diagnosis of typhoid fever with high sensitivity as well as accuracy for identification of typhoid fever, the rapid diagnostic test (Dot Elisa) is better than the Widal test. However, it may be an increased burden to healthcare owing to a low positive predictive value in a low prevalence scenario.